Undergraduates' use of metacognitive strategies in a PBL writing process - Aliyu, Muhammad Mukhtar; Yong, Mei Fung (ELT Forum: Journal of English Language Teaching, 2020)
This study examines the use of metacognitive strategies in undergraduates' PBL writing process. The participants of the study are 18 second-year undergraduates in an intact class of Advanced Composition in a university in North-eastern Nigeria. Data for the study were collected through audio and video recordings of the participants' interactions in the PBL process. The findings of the study showed the PBL allowed the participants to effectively use metacognitive strategies: planning, monitoring, and evaluation in various ways to achieve their writing goals. For the planning process, the participants made an overall plan of their writing process, generated various ideas, retrieved their rhetorical and linguistic knowledge, and made decisions on what and how to present ideas in their writing. For monitoring, they kept track of the transition of ideas and paragraphs in their writing and identify and remedy problems that affect the writing progress. For evaluation, they evaluated the content, organisation, and language of their writing. The paper makes some recommendations for teachers to assist students in the use of metacognitive strategies which eventually improve their writing skills.